(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe mothers’ knowledge of caring for children under 2 years old with acute diarrhea at Thai Binh Pediatric Hospital. Methods: A cross-sectional descriptive study was conducted on 119 mothers of children under 2 years old with acute diarrhea, from September 2025 to April 2026. Data were collected using a 36-item questionnaire covering general information, knowledge of acute diarrhea, Oresol and fluid-electrolyte replacement, nutrition, hygiene, and medication use. Results: Mothers’ knowledge remained limited. The correct response rate for the definition of acute diarrhea was 45.4%; appropriate diet was 32.8%; and recognition of dehydration signs through skin turgor and sunken fontanel was 25.2% and 30.3%, respectively. Knowledge of Oresol was 45.4%, while correct understanding of preparation ranged from 37.8% to 78.2%. The proportions of correct knowledge regarding zinc supplementation and avoiding self-medication were 52.1% and 42.9%, respectively. Overall 68.9% of mothers had inadequate knowledge, while only 31.1% achieved the required level (≥ 75%). Conclusion: Mothers’ knowledge of caring for children with acute diarrhea remains insufficient, particularly in recognizing dehydration, nutritional management, and Oresol use. Health education interventions are needed to improve caregiving knowledge and practices.